PERANCANGAN SISTEM INFORMASI ABSENSI DI PT. BRAINCODE SOLUTION - Gustiana, Iyan (Gaung Informatika, 2012)
The increase in the number of employees should be appropriate with improved service facilities and amenities adequate system performance is expected to occur. Likewise, the absence facilities that seem trivial but it will have a serious impact if not addressed seriously. NIK input process with a certain length of time in the size range by the number of queue to do the same. It keeps the pressure psychological and cause errors in inputting NIK itself . The reason and purpose of the research is to design information systems that have an integrated database in the HR and payroll so that attendance data can be processed. The methodology uses a systems structured methode. The result is an information system with an integrated database.